Point-of-View Recording Devices for Intraoperative Neurosurgical Video Capture - Porras, Jose L.; Khalid, Syed; Root, Brandon K.; Khan, Imad S.; Singer, Robert J. (Frontiers in Surgery, 2016)
Abstract Introduction: The ability to record and stream neurosurgery is an unprecedented opportunity to further research, medical education, and quality improvement. Here, we appraise the ease of implementation of existing POV devices when capturing and sharing procedures from the neurosurgical operating room, and detail their potential utility in this context. Methods: Our neurosurgical team tested and critically evaluated features of the Google Glass and Panasonic HX-A500 cameras including ergonomics, media quality, and media sharing in both the operating theater and the angiography suite. Results: Existing devices boast several features that facilitate live recording and streaming of neurosurgical procedures. Given that their primary application is not intended for the surgical environment, we identified a number of concrete, yet improvable, limitations. Conclusion: The present study suggests that neurosurgical video capture and live streaming represents an opportunity to contribute to research, education, and quality improvement. Despite this promise, shortcomings render existing devices impractical for serious consideration. We describe the features that future recording platforms should possess to improve upon existing technology.